2022
DOI: 10.1021/acs.energyfuels.2c02851
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Small Crystal Size Y Zeolite Catalysts with High Hydrocracking Performance on n-Hexadecane

Abstract: A series of in situ dodecyl trimethyl ammonium bromide (DTAB)-modified small-crystal Y zeolites have been successfully synthesized by DTAB addition to the seed synthesis procedure, which was used to create the small crystal size Y zeolites. Compared to the Y zeolites prepared without DTAB, the Y zeolites prepared with DTAB have a uniform morphology and mesoporous structure, a larger specific surface area (up to 32.3 m 2 g −1 increase), a smaller crystal size (up to 66 nm reduction), and more Bronsted acid site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…X-ray photoelectron spectroscopy (XPS) of the sulfided catalysts was performed on a VG ESCA Lab 250 spectrometer with Al Kα rays, and the Al 2p peak (74.6 eV) was selected as the reference. The sulfidation degree of metal W and metal Ni of the sulfided catalysts was calculated according , to eqs and : Sulfidation degree of W: .25em italicW sul = normalW normalS 2 normalW normalS 2 + normalW normalO x normalS y + normalW normalO 3 Sulfidation degree of Ni: .25em normalN normali sul = normalN normali normalS x + NiWS normalN normali normalS x + NiWS normali normalW normalS + NiO Among them, the name of each substance represents their content.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray photoelectron spectroscopy (XPS) of the sulfided catalysts was performed on a VG ESCA Lab 250 spectrometer with Al Kα rays, and the Al 2p peak (74.6 eV) was selected as the reference. The sulfidation degree of metal W and metal Ni of the sulfided catalysts was calculated according , to eqs and : Sulfidation degree of W: .25em italicW sul = normalW normalS 2 normalW normalS 2 + normalW normalO x normalS y + normalW normalO 3 Sulfidation degree of Ni: .25em normalN normali sul = normalN normali normalS x + NiWS normalN normali normalS x + NiWS normali normalW normalS + NiO Among them, the name of each substance represents their content.…”
Section: Methodsmentioning
confidence: 99%
“…X-ray photoelectron spectroscopy (XPS) of the sulfided catalysts was performed on a VG ESCA Lab 250 spectrometer with Al Kα rays, and the Al 2p peak (74.6 eV) was selected as the reference. The sulfidation degree of metal W and metal Ni of the sulfided catalysts was calculated according , to eqs and : Among them, the name of each substance represents their content.…”
Section: Methodsmentioning
confidence: 99%
“…The usual experimental verification of the absence of diffusional limitation consists in varying the crystal size; in a reaction-controlled regime, the crystal size should not have any impact on the reaction rate. In practice, however, it is challenging to vary the size of zeolite crystals without changing at the same time their acidity, which makes interpreting kinetics as a function of crystal size extremely difficult …”
Section: Basics Of Catalysis By Zeolitesmentioning
confidence: 99%
“…In recent years, many studies have been reported on the production of jet fuel or other fractions by hydrocracking and isomerization reactions using hydrocarbons from n -C15 to n -C18 as a model of hydrotreated fat or FT wax, biodiesel of fatty acid methyl ester and fats, etc. because jet fuel is considered to be highly likely to be liquid in the future due to various factors. The hydrocracking catalyst needs to arrange the cracking and isomerization abilities in order to achieve high selectivity for the intermediate fraction.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrocracking catalyst needs to arrange the cracking and isomerization abilities in order to achieve high selectivity for the intermediate fraction. For this reason, the preparation of catalysts which can regulate cracking activity by changing the type, content, and SiO 2 /Al 2 O 3 ratio of a zeolite in the catalyst has been investigated. Although n -hexadecane has usually been used so far, a high yield of jet fuel fraction has not been achieved. Further studies of n -heptadecane are very few …”
Section: Introductionmentioning
confidence: 99%